1996
DOI: 10.2307/3433154
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Environmental Benzene Exposure

et al.

Abstract: Environmental exposures to benzene result in increases in body burden that are reflected in various biomarkers of exposure, including benzene in exhaled breath, benzene in blood and urinary trans-trans-muconic acid and S-phenylmercapturic acid. A review of the literature indicates that these biomarkers can be used to distinguish populations with different levels of exposure (such as smokers from nonsmokers and occupationally exposed from environmentally exposed populations) and to determine differences in meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 10 publications
0
15
0
1
Order By: Relevance
“…Fustinoni et al (2005) reviewed a range of 3-18%. Weisel et al (1996) reported that in exposure level below 100 ppm, the fraction of metabolite excreted as t,t-MA (f t,t-MA ) is 21% of the total metabolite.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fustinoni et al (2005) reviewed a range of 3-18%. Weisel et al (1996) reported that in exposure level below 100 ppm, the fraction of metabolite excreted as t,t-MA (f t,t-MA ) is 21% of the total metabolite.…”
Section: Resultsmentioning
confidence: 99%
“…So a lower value of f t,t-MA give rise to higher estimated body burden. Hence to avoid over estimation we have used the highest reported value by Weisel et al (1996) in our calculation. Such fraction of urinary excretion for a targeted biomarker has been used previously to estimate internal dose of Benzene using pharmacokinetic model (Schettgen et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Any of these quantities could be considered a "biomarker of exposure." Examples of the kinds of analytical tests performed to measure biomarkers of exposure include obtaining serum lead levels, measuring trans, trans muconic acid in urine to test for benzene exposure, or obtaining breath samples to detect benzene directly (Weisel et al, 1996). Frequently these analytical tests are performed to gauge the level of "biologic plausibility" of relating an exposure to a particular chemical to the Wnding of a disease state or other negative outcome.…”
Section: Three Classes Of Biomarkersmentioning
confidence: 99%
“…Sie können Substanzen, Strukturen oder Prozesse umfassen, wobei 3 verschiedene Typen unterschieden werden [35]: [36]. Biomarker können eine sorgfältige Expositionsermittlung nicht generell ersetzen.…”
Section: Anwendungsbereicheunclassified